Spectral element method for three dimensional elliptic problems with smooth interfaces - Khan, Arbaz; Husain, Akhlaq; Mohapatra, Subhashree; Upadhyay, Chandra Shekhar (Computer methods in applied mechanics and engineering, 2017)
In this paper we propose a least-squares spectral element method for three dimensional elliptic interface problems. The differentiability estimates and the main stability theorem, using non-conforming spectral element functions, are proven. The proposed method is free from any kind of first order reformulation. A suitable preconditioner is constructed with help of the regularity estimate and proposed stability estimates which is used to control the condition number. We show that these preconditioners are spectrally equivalent to the quadratic forms by which we approximate them. We obtain the error estimates which show the exponential accuracy of the method. Numerical results are obtained for both straight and curved interfaces to show the efficiency of the proposed method.